Physical Activity, Food Consumption and Nutritional Status among Female High School Students in North Denpasar - Nabila Zuhdy; Luh Seri Ani; Ni Wayan Arya Utami (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: Optimal nutrition status will lead to health and productive adolescent. Recently, double burden of nutritional status has occurred among adolescent, including underweight and overweight. This study assessed that relationship among adolescent in urban area. Methods: This study was cross-sectional survey with a total sample of 75 female students who were randomly selected from three high schools. Data were collected by interviews using a structured questionnaire, Semi-quantitative Food Frequency Questionnaire (SQFFQ) and Adolescent Physical Activity Recall Questionnaires (APARQ). Anthropometric measurement was done for height, weight, middle upper arm and stomach circumference. Data of food consumption were analyzed using software Nutri-Survey, WHO Anthro Plus. Thecorrelation of risk factor and nutritional status were tested by linier regression. Results: This study supports the evidence of double burden in nutritional status among high school female students. Despite 18,67% of chronic energy deficiency, 8% students were overweight. Consumption of snack and fast food was also frequent, that may relate to high level of fat sufficiency among them. Variable significantly associated in all indicators of nutritional status was weight control (p<0.05). Physical activities had no significant relationship to nutritional status. Conclusion: There was double burden of nutritional status among high school female students especially overweight. Weight control had significant relationship toward nutritional status, while physical activities had no significant relationship to nutrition status.